Associations of the Mediterranean-Dietary Approaches to Stop Hypertension Intervention for Neurodegenerative Delay diet with cardiac remodelling in the community: the Framingham Heart Study. Issue 12 (28th December 2021) - Walker, Maura E.; O'Donnell, Adrienne A.; Himali, Jayandra J.; Rajendran, Iniya; Melo van Lent, Debora; Ataklte, Feven; Jacques, Paul F.; Beiser, Alexa S.; Seshadri, Sudha; Vasan, Ramachandran S.; Xanthakis, Vanessa
Abstract: Normal cardiac function is directly associated with the maintenance of cerebrovascular health. Whether the Mediterranean-Dietary Approaches to Stop Hypertension Intervention for Neurodegenerative Delay (MIND) diet, designed for the maintenance of neurocognitive health, is associated with cardiac remodelling is unknown. We evaluated 2512 Framingham Offspring Cohort participants who attended the eighth examination cycle and had available dietary and echocardiographic data (mean age 66 years; 55 % women). Using multivariable regression, we related the cumulative MIND diet score (independent variable) to left ventricular (LV) ejection fraction, left atrial emptying fraction, LV mass (LVM), E / e ' ratio (dependent variables; primary), global longitudinal strain, global circumferential strain (GCS), mitral annular plane systolic excursion, longitudinal segmental synchrony, LV hypertrophy and aortic root diameter (secondary). Adjusting for age, sex and energy intake, higher cumulative MIND diet scores were associated with lower values of indices of LV diastolic ( E / e ' ratio: log β = −0·03) and systolic function (GCS: β = −0·04) and with higher values of LVM (log β = 0·02), all P ≤ 0·01. We observed effect modification by age in the association between the cumulative MIND diet score and GCS. When we further adjusted for clinical risk factors, the associations of the cumulative MIND diet score with GCS in participants ≥66 years ( β = −0·06, P = 0·005) and LVM remained significant. In our community-based sample, relations between the cumulative MIND diet score and cardiac remodelling differ among indices of LV structure and function. Our results suggest that favourable associations between a higher cumulative MIND diet score and indices of LV function may be influenced by cardiometabolic and lifestyle risk factors.